Sacred Sounds and Waters: Sonic and Scientific Dimensions of Divine Connection in Ethiopian Orthodox Christianity, Oromo Irreecha, and Global Traditions - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
This study explores the synergistic roles of water and sound in facilitating divine connection and cultural expression across Ethiopian Orthodox Christianity’s Tsebel rituals, the Oromo Irreecha festival, and global religious traditions, integrating scientific perspectives to elucidate their efficacy. In Ethiopian Orthodox Christianity, Tsebel (holy water) is central to sacraments like baptism and healing, with Timkat’s communal immersions and liturgical hymns fostering spiritual communion. Similarly, Irreecha’s September riverside rituals involve songs and grass offerings to Waaqaa, symbolizing gratitude and renewal. Global parallels, including Hindu Ganges mantras, Islamic Zamzam recitations, Shinto misogi chants, and Indigenous water songs, reveal water and sound as universal conduits for divine communication. Scientific insights enhance understanding: water’s acoustic properties (transmitting sound four times faster than air) create immersive ritual environments, while chanting reduces stress hormones and triggers dopamine, promoting transcendence. Physiologically, water’s 60% composition in the human body mirrors its symbolic clarity, with placebo effects supporting perceived healing. These findings highlight how water and sound unite communities, reinforce cultural identity, and foster environmental stewardship, as seen in Irreecha’s nature-centric offerings. Future research could explore lesser-known rituals or neuroscientific impacts of sound in aquatic settings. This interdisciplinary analysis contributes to religious studies, anthropology, and science, emphasizing the universal human quest for divine connection through elemental forces. By documenting these practices, the study supports cultural preservation amid modernization, offering insights into humanity’s spiritual resilience.